SKIN ANTISEPSIS PRACTICES FOR CENTRAL NEURAXIAL BLOCKADE - Nisar, Abdullah; Rehman, Azhar; Siddiqui, Ali Sarfraz (Journal of Ayub Medical College Abbottabad, 2024)
Background: Skin antisepsis is essential before the central neuraxial blockade. Various antiseptic solutions are in clinical use, like povidone-iodine, alcohol, or chlorhexidine. This study was conducted to assess current practices for skin antisepsis before central neuraxial blockade and observe the compliance of anaesthesiologists with international standards in Teaching Hospitals in Karachi, Pakistan. Methods: A cross-sectional study was conducted on all anaesthesia faculty members, working in Teaching Hospitals in Karachi from March to May 2022. Demographic data included institutional setup and current position at the institution. The type of solution used for skin anti-sepsis for the central neuraxial blockade, method of application, and subsequent practices of anti-sepsis were asked. Recommendations for the skin anti-antisepsis and the reason for opting for their choice of solution and practices were also assessed. Stratification analysis was then performed to observe the effect modifiers of study variables. Results: Data from seventy faculty members were analyzed. Povidone-Iodine was the most frequent solution used for skin antisepsis. Alcohol-based Chlorhexidine 2% and 0.5% were the alternative choices. The application method prevalent was Sponge/swab with Gallipot (94.3%). Major reasons to opt for their choice of solution were personal preference, cost-effectiveness, and availability of the solution in their Institute. Fifty percent of physicians considered Chlorhexidine 2% as the recommended solution for central neuraxial procedures. Regarding sterility, over ninety percent adhered to the recommended practices. Conclusion: Povidone-Iodine is currently the most frequent solution used for skin antisepsis before central neuraxial blockade by anaesthesiologists. The recommended solution (Chlorhexidine) was not in clinical practice due to personal preference, cost-effectiveness, or unavailability.